Carbon quantum dots aqueous solution as electrolyte for H2O2 production based on photoelectrochemical water splitting. Issue 8 (2nd February 2023) - Wang, Na; Zhang, Yong-Shuai; Wei, Dong-Dong; Duan, Hui-Min; Mo, Liu-Meng; Wang, Hong-Yan
Abstract : H2 O2 accumulation on the BiVO4 photoanode via PEC water oxidation was achieved with carbon quantum dots aqueous solution as an electrolyte. The development can hopefully draw more attention to catalytic media for tailoring PEC performance. Abstract : Modulation of electrolyte to tailor the activity and selectivity for photoelectrochemical (PEC) water splitting has been long neglected. Herein, we boosted H2 O2 accumulation on a BiVO4 photoanode via PEC water oxidation in a series of carbon quantum dots (CQDs) aqueous solutions with aliphatic amino acids as precursors. Mott–Schottky measurements demonstrated CQDs solution can tune catalytic voltage location of the BiVO4 substrate. Open circuit voltage decay (OCVD) demonstrated that the system can achieve efficient charge separation owing to the fabricated dynamic heterojunction between CQDs particles and BiVO4 substrate. Owing to the energy gradient, water oxidation may occur on the more hydrophilic CQDs surface, which regulated H2 O2 generation mediated by the formation of hydroxyl radicals (OH˙) from water, as evidenced by electron paramagnetic resonance (EPR). Assisted by a Clark electrode and linear sweep voltammetry, we evidenced that CQDs can efficiently retard H2 O2 decomposition. Overall, H2 O2 production was performed with a rate averaging 0.33 μmol min −1 cm −2 at 1.23 V with a Faraday efficiency (FE) of 93.5%, in which O2 evolution was nearly completely suppressed. By contrast, the commonly used HCO3 − electrolyte only afforded an H2 O2 evolution rate of 0.032 μmol min −1 cm −2, corresponding to FE of 18.2%. Here, we executed PEC water oxidative H2 O2 accumulation in CQDs solution directly, and the innovation can hopefully draw more attention to catalytic media for improving PEC performance.